SWOT Analysis for Innovative Product of Patchouli Derivatives and Coffee Grounds Aromatherapy Candle As a Mosquito Natural Insecticide - Sahla, Sadira; Ariq, Muhammad; Fadlianur, Azzahiri; Rachman, Arief; Munawarah, Auliatul (Universitas Syiah Kuala, 2023)
The humid environment facilitates the survival and proliferation of Aedes aegypti mosquitoes. Nowadays, there are many chemically-based mosquito repellents available in the market. However, instead of eliminating the diseases or problems caused by mosquitoes, these chemical insecticides actually give rise to new issues such as respiratory disturbances in humans. Therefore, an innovation has emerged to create OMWIS which is a botanical mosquito insecticide. The puIDRose of this study is to analyze business feasibility and develop a strategy for developing OMWIS innovative products using the SWOT analysis method internally (strengths and weaknesses) and externally (opportunities and threats). This type of research is descriptive qualitative and quantitative research using SWOT analysis. The results of the SWOT analysis matrix for OMWIS products based on the SO strategy indicate to maintain and expand cooperation with suppliers of coffee grounds, continue to develop product and packaging innovations, maintain a lower price compared to conventional mosquito repellents, and position it as an effective natural room freshener. The advantages of OMWIS compared to similar products are that it is made from natural and safe materials for both humans and the environment, serving as both aromatherapy and mosquito repellent, providing a longer-lasting fragrance due to the addition of heavy fraction patchouli essential oil, practical and easy to use, premium packaging to preserve product integrity and portability, and affordable pricing, even cheaper than similar products. With a selling price of IDR 65,000/90 mL jar, OMWIS generates a profit of IDR 21,606/jar and making it as viable business venture.Keywords:citronella, patchouli, lemon, coffee grounds, natural insecticides, mosquito, aroma therapy, OMWIS